Water stress and temperature effects on germination and early seedling growth of Digitaria eriantha - Brevedan, Roberto (2013)
This study focused on the two major processes critical for plant establishment: Seed germination and seedling survival. We determined the effects of (1) water stress and temperature on the germination, and (2) water stress on early seedling growth of Digitaria eriantha cv ‘Irene’. Seeds harvested in 2007 were used for temperature studies, and those coming from 2006 and 2007 for water stress studies. In 2009, viability decreased by 65.4% from 2006 to 2007. During the first twenty-four hours, germination was more than 50% at constant (30 or 35°C) than alternating (10/30 or 10/35°C) temperatures, although total germination was about 80% for all temperature treatments. Polyethylene glycol 8000 was used to impose water stress conditions. Germination percentages and coefficients of velocity decreased with decreasing water potentials. Early seedling growth was smaller at lower water potentials. D. eriantha cv ‘Irene’ appeared to germinate within a wide range of temperatures, but it varied greatly in germination response to water potentials. Results suggest that this species could be planted in late spring-early summer, when seedbed temperatures are increasing and soil moisture might still be adequate.